2020
DOI: 10.1002/mrm.28240
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of velocity‐selective arterial spin labeling settings for placental perfusion measurement

Abstract: Purpose Placental function is key for successful human pregnancies. Perfusion may be a sensitive marker for the in vivo assessment of placental function. Arterial spin labeling (ASL) MRI enables noninvasive measurement of tissue perfusion and it was recently suggested that ASL with velocity‐selective (VS) labeling could be advantageous in the placenta. We systematically evaluated essential VS‐ASL sequence parameters to determine optimal settings for efficient placental perfusion measurements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…For clarity data points are slightly shifted with respect to each other at each post-labelling delay and one-sided error bars are shown. pCASL pseudo-continuous arterial spin labelling, PWS perfusion weighted signal few studies have already shown promising results of flowbased ASL imaging in the abdomen for the kidneys [31,32] and placenta [33,34] in adults. Another recent study in paediatric patients with Moyamoya has shown VSASL offers a powerful approach to accurately image perfusion in these patients due to transit delay insensitivity [35].…”
Section: Discussionmentioning
confidence: 99%
“…For clarity data points are slightly shifted with respect to each other at each post-labelling delay and one-sided error bars are shown. pCASL pseudo-continuous arterial spin labelling, PWS perfusion weighted signal few studies have already shown promising results of flowbased ASL imaging in the abdomen for the kidneys [31,32] and placenta [33,34] in adults. Another recent study in paediatric patients with Moyamoya has shown VSASL offers a powerful approach to accurately image perfusion in these patients due to transit delay insensitivity [35].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, MRI has proved to be a panoply in understanding the human placenta and its role in determining lifetime outcomes. Together with extensive innovation in adapting MRI techniques, many recent studies have provided invaluable information on the structure, function and biochemistry of the placenta across gestation ( Siauve et al, 2015 ; Porras et al, 2017 ; Rajagopalan et al, 2017b ; Harteveld et al, 2020 ). Further, this research is being extended to understand how pathophysiological conditions in the placenta or the fetus interact with the other ( Andescavage et al, 2015 ; Zun and Limperopoulos, 2018 ; Luo et al, 2017 ; León et al, 2018 ).…”
Section: Unique Qualities Of Fetal Mri For Advancing Sciencementioning
confidence: 99%
“…Another advantage of flow‐sensitized ASL is that placement of a labeling slab is not required, simplifying the planning of the ASL examination, which can be complicated in the kidneys. Thus far, flow‐sensitized perfusion measurements have been demonstrated primarily in the brain, 11,13,14,16,17 with recent applications in the heart 18,19 and placenta 20,21 . We recently investigated the feasibility of VSASL labeling in the kidney at 1.5 T, and demonstrated that with properly chosen VSASL sequence parameters, labeling and subtraction artifacts due to (respiratory) motion can be avoided, and with that showed feasibility of VSASL for renal perfusion measurements 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, flow-sensitized perfusion measurements have been demonstrated primarily in the brain, 11,13,14,16,17 with recent applications in the heart 18,19 and placenta. 20,21 We recently investigated the feasibility of VSASL labeling in the kidney at 1.5 T, and demonstrated that with properly chosen VSASL sequence parameters, labeling and subtraction artifacts due to (respiratory) motion can be avoided, and with that showed feasibility of VSASL for renal perfusion measurements. 22 Because a low V C in the presence of respiratory motion can cause spurious labeling of moving tissue, a higher V C is advised for the kidney than, for example, for the brain (≈ 2 cm/s) with velocity-encoding direction perpendicular to the primary direction of respiratory motion.…”
Section: Introductionmentioning
confidence: 99%